The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.tcm.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

“Beauty is a light in the heart”: The transformative potential of optogenetics for clinical applications in cardiovascular medicine1

Abstract: Optogenetics is an exciting new technology in which viral gene or cell delivery is used to inscribe light sensitivity in excitable tissue to enable optical control of bioelectric behavior. Initial progress in the fledgling domain of cardiac optogenetics has included in vitro expression of various light-sensitive proteins in cell monolayers and transgenic animals to demonstrate an array of potentially useful applications, including light-based pacing, silencing of spontaneous activity, and spiral wave terminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 47 publications
(81 reference statements)
0
45
0
Order By: Relevance
“…Cardiac optogenetics is an exciting new field in which cells in the heart are genetically modified to express light-sensitive proteins (opsins) so that low-energy light can be used to induce transmembrane current, providing a means for electrophysiological control (1,2). Many different types of opsins exist, including ionic channels and pumps that produce different types of membrane current (i.e., depolarizing or hyperpolarizing) when illuminated with light in a particular wavelength range (3-8); this rich diversity means that optogenetics enables numerous useful applications in opsin-expressing tissue, including eliciting or suppressing action potentials (APs) with exquisite spatiotemporal specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac optogenetics is an exciting new field in which cells in the heart are genetically modified to express light-sensitive proteins (opsins) so that low-energy light can be used to induce transmembrane current, providing a means for electrophysiological control (1,2). Many different types of opsins exist, including ionic channels and pumps that produce different types of membrane current (i.e., depolarizing or hyperpolarizing) when illuminated with light in a particular wavelength range (3-8); this rich diversity means that optogenetics enables numerous useful applications in opsin-expressing tissue, including eliciting or suppressing action potentials (APs) with exquisite spatiotemporal specificity.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to model light-tissue interactions is to track the behavior of individual photon packets in heart tissue via Monte Carlo methods (79). This approach results in a highly accurate approximation of the 3D distribution of irradiance resulting from cardiac illumination, including subtle effects such as the sub-surface energy peak caused by photon back-scattering (76); however, it is computationally intense (79) and representation of back-scattering is considered non-essential in the context of cardiac optogenetics (2), since the primary light-related constraint is the fact that opsin-exciting light cannot penetrate very deeply in cardiac tissue. An appropriate and computationally expedient alternative is to approximate model attenuation effects by solving the steady state photon diffusion equation, which assumes homogeneous absorption and isotropic scattering in the cardiac tissue: D2normalEe(boldr)μnormalanormalEe(boldr)=w(boldr) where E e and w are, respectively, the distributions of irradiance and photon sources at each point r; ∇ 2 is the Laplace operator; D is the diffusivity of light in the medium (which depends on absorption and scattering characteristics); and μ a is the tissue-specific rate of light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…These in silico simulations are discussed in the current review [4] and revealed that both approaches can putatively enable optical pacing of the ventricular myocardium. However, the simulations are based on the assumptions that gene delivery results in sufficient ChR2 expression in enough cells and that cell delivery leads to stable engraftment and functional coupling of transplanted cells to the host myocardium, which both has not been verified in vivo yet.…”
mentioning
confidence: 94%
“…In this issue of Trends in Cardiovascular Medicine, Boyle et al [4] review the existing literature on optogenetic control of heart muscle in vitro, in silico, and in vivo and discuss the potential clinical use to treat cardiac arrhythmia. Because optogenetic stimulation has distinct advantages over electrical stimulation such as low energy consumption, cell-specific stimulation, uniform de-or hyperpolarization, and high spatial precision, optogenetic cardiac pacing or defibrillation can be envisioned in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation